Identifying the effects of technology acceptance model constructs on small-scale renewable energy adoption in rural contexts - Kurmanov, Nurlan; Kabdullina, Gulmira; Kenzhin, Zhaxat; Zhambylova, Gulfiya; Kabdolla, Asylkhan; Adilbekuly, Merey (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the adoption of small-scale renewable energy technologies on farms and in rural households. The research problem arises from fragmented and heterogeneous empirical findings obtained in studies based on the technology acceptance model (TAM), which prevent the formation of quantitatively substantiated conclusions regarding the role of key behavioral determinants of renewable energy adoption. This study identifies and quantitatively synthesizes the effects of perceived usefulness and perceived ease of use on intention and actual adoption behavior within a theoretically focused and statistically rigorous framework. Eight independent studies with a total sample of 2,675 respondents were included. Effect sizes were aggregated using random-effects models and estimated through Fisher’s Z transformation. The results reveal robust and statistically significant positive effects of both perceived usefulness and perceived ease of use on adoption behavior. However, perceived usefulness demonstrates a more stable and structurally consistent influence across rural contexts. The findings indicate that adoption decisions are primarily driven by expected economic and functional benefits, highlighting the importance of emphasizing the practical value of renewable energy technologies in rural implementation strategies. The distinctive feature of the study lies in its exclusive focus on core TAM constructs and systematic aggregation of effect sizes within rural small-scale renewable energy contexts. The results can be applied in the design of public policies and support programs aimed at enhancing perceived usefulness of renewable energy technologies under conditions of rural economic and infrastructural constraints